Biodegradable Container for Planting Purpose - Abdullah Afendi, Ain Afifa; Harun, zawati; Hairom, Nur Hanis Hayati; Yaakob, Maizatulazrina Yaakob; Norsuhailizah Sazali; Rosniza Hussin; Zakiah Kamdi; Mohd Riduan Jamalludin; Siti Khadijah Hubadillah (Emerging Advances in Integrated Technology, 2026)
Amid growing environmental concerns and the escalating plastic pollution crisis, the use of containers from fiber natural materials, which can decompose naturally over time, offer a promising solution to reduce the ecological impact due to plastic waste. The study aligns with the global commitment to create a more sustainable and environmentally conscious future. It holds critical importance in the context of environmental sustainability and the advancement of sustainable agricultural practices. This research study aimed to identify suitable fibers for the fabrication of biodegradable containers and explored various materials such as recycled paper, rice straw, corn husk, and coconut fiber, and analyzed their characteristics and properties once fabricated into containers. Several experiments were conducted to find out how different types of fiber containers influence the soil humidity pH of soil, soil salinity and ease the plant growth by providing nutrient. It was found that combination of rice straw and recycled paper container facilitated the most significant of plant growth while combination of coconut fiber and recycled paper container is the fastest in degradation. Overall comparison also shows that sample container mixed fiber able to give better results as compared to sample with recycled paper only. Thus, the new developments of  biodegradable materials from agriculture waste  not only able to reduce toxic waste from plastic  and the abundant of agrowaste problem but also able to give benefit for the plant growth and agriculture yield production.